Accuracy of colposcopy-directed biopsy in detecting early cervical neoplasia: a retrospective study - Stuebs, Frederik A.; Schulmeyer, Carla E.; Mehlhorn, Grit; Gaß, Paul; Kehl, Sven; Renner, Simone K.; Renner, Stefan; Geppert, Carol-Immanuel; Adler, Werner; Hartmann, Arndt; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2019)
PurposeColposcopy-directed biopsy is a cornerstone method for diagnosing cervical intraepithelial neoplasia. The aim of this study was to evaluate the accuracy of colposcopy-directed biopsy in comparison with definitive surgery.MethodsThe accuracy of colposcopy-directed biopsy was compared with the final histology in relation to different types of transformation zone (TZ), the patient's age, and the examiner's level of training.ResultsThe overall accuracy of biopsy in comparison with definitive surgery was 71.9% for all entitiesbenign lesions, low-grade squamous intraepithelial lesions, high-grade squamous intraepithelial lesions (HSILs), and cervical carcinomawith an underdiagnosis rate of 11.8% and an overdiagnosis rate of 16.5%. The accuracy for detecting HSIL was 88% (401/455), with an underdiagnosis rate of 10.5% and overdiagnosis rate of 1.3%. The accuracy rates for detecting HSIL in women with TZ1, TZ2, or TZ3 were 92.2, 90.5, and 76.5%, respectively. The accuracy rates for detecting HSIL in the different age groups were 93.1% (age 0-34), 83.6% (age 34-55), and 80% (age 55 or older).ConclusionsA combination of the colposcopic findings, cytology, human papillomavirus testing, and colposcopy-directed biopsy is necessary for the correct diagnosis of HSIL. The accuracy rate depends on the TZ and the patient's age. The examiner's level of training does not have any substantial influence on the accuracy.
CRIS-Team WoS Importer:2019-03-08